2020
DOI: 10.1155/2020/5086049
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Surface Subsidence Extension due to Underground Caving: A Case Study of Hemushan Iron Mine in China

Abstract: Underground caving can potentially lead to large-scale surface destruction. To test the safety conditions of the surface construction projects near the circular surface subsidence zone in the Hemushan Iron Mine, this paper proposes an analytical model to analyze the stability of the cylindrical caved space by employing the long-term strength of the surrounding rock mass, the in situ stress, and the impact of caved materials as inputs. The proposed model is valid for predicting the orientation and depth where r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…For example, backfilling of the subsidence pit is suggested for caving-based cases, so as to prevent the subsequent extension of surface subsidence after vertical caving. Such prevention has been validated in the Hemushan and Gongchanling iron mines [56]. Moreover, three approaches, i.e., using industrial wastes (such as fly ash or alkali-activated slag [57,58]) as cementing materials to reduce the consumption of cement in the backfilling stage, employing energy-efficient pumps, and further developing hauling systems, especially LHDs, are recommended for filling-based projects to mitigate their GHG emissions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, backfilling of the subsidence pit is suggested for caving-based cases, so as to prevent the subsequent extension of surface subsidence after vertical caving. Such prevention has been validated in the Hemushan and Gongchanling iron mines [56]. Moreover, three approaches, i.e., using industrial wastes (such as fly ash or alkali-activated slag [57,58]) as cementing materials to reduce the consumption of cement in the backfilling stage, employing energy-efficient pumps, and further developing hauling systems, especially LHDs, are recommended for filling-based projects to mitigate their GHG emissions.…”
Section: Discussionmentioning
confidence: 99%
“…e overlying rock mass appears to move and destroy caused by the underground mining method, such as the room and pillar mining method [1,2] and the caving mining method [3,4]. Gradually, this deformation expands upward to the surface with the development of new cracks and the expansion of primary cracks [5]. e mine area for underground mining may be forced to be closed when the surface strata movement seriously threatens the safety of surface structures, such as roads, bridges, and open pits.…”
Section: Introductionmentioning
confidence: 99%
“…Castro et al [24][25][26][27][28][29] proposed a mining theory of high sublevel and large drift spacing based on the ore drawing theory, adjusted the sublevel height and drift spacing in different mines accordingly, and implemented it. In addition, extensive literature indicated that the decreased ore loss and dilution rate depended on the reasonable stope structure parameters [30][31][32][33][34][35][36]. Tan et al [37] proved that the optimization of stope structural parameters based on ellipsoid arrangement theory was not rigorous and perfect, which did not follow the consistent principle of the blasted ores and IEZ's shape in essence.…”
Section: Introductionmentioning
confidence: 99%